Green target costing and its role in improving quality: Review paper: green target cost (Entrepreneurship Journal for Finance and Business, 2024)
This study aims to explain the cognitive foundations of green target costing, its role in reducing costs, and the extent of its contribution to environmental protection by reducing pollution and reducing consumption of resources and energy, in addition to improving quality and reducing the costs of environmental failure, that is, achieving a balance between environmental responsibility and reducing costs, as well as how to introduce aspects The environment in the target cost equation. In order to achieve this goal, the study used philosophical analysis of its variables, in addition to a review of the literature that searched for the traditional target cost all the way to the green one, as a sample of studies limited to the years 2004 - 2023 was taken. This study concluded the importance of the green target cost in Achieving a balance between product quality, cost and environmental responsibility, and how it can contribute to improving quality and reducing the costs of failure.